Drug-induced dermatomyositis: a pharmacovigilance study of the FDA adverse event reporting system - Bi, Jianing; Xie, Hanzhang; Yang, Yixuan; Chen, Qiaochu; Cui, Bingnan; Xiao, Zhanshuo (Frontiers in Pharmacology, 2025)
BackgroundDermatomyositis (DM) is an autoimmune disease that may be triggered by certain medications. However, most studies have focused on specific drugs, lacking a comprehensive overview. This study uses the FDA’s Adverse Event Reporting System (FAERS) to explore the correlation between DM and medications.Research design and methodsThe study encompassed FAERS reports from January 2004 to June 2024. We coded and classified adverse events (AEs) using MedDRA and conducted multiple disproportionality analyses (ROR, PRR, BCPNN, MGPS) to examine drug-event associations and analyze the results.ResultsUsing the “primary suspects” role code in FAERS, 1767 reports involving 353 drugs suspected of inducing DM were identified. Among 24 signal-positive drugs, cardiovascular drugs (297 reports, mainly statins) were most frequent, followed by immunotherapy agents (188 reports, mainly Immune Checkpoint Inhibitors) and chemotherapy agents (147 reports, mainly Antimetabolites).ConclusionThis study on drug-induced DM presents a new approach to rational and evidence-based drug prescribing. It leverages advanced model algorithms to significantly improve the precision in predicting drug-DM correlations, enhancing patient safety. Additionally, the study provides clinicians with guidance on avoiding medications associated with DM in patients with predisposing factors that may increase their risk of developing the condition.